Surface characterization and functional properties of carbon-based materials - Nelson, GW (2012)
Carbon-based materials are poised to be an important class of 21st century materials, for bio-medical, bio-electronic, and bio-sensing applications. Diamond and polymers are two examples of carbon-based materials of high interest to the bio-materials community. Diamond, in its conductive form, can be used as an electrochemical bio-sensor, whilst its nanoparticle form is considered a non-inflammatory platform to deliver drugs or to grow neuronal cells. Polymers, especially when chemically modified, have been used extensively in biological environments, from anti-microbial use to drug delivery. The large-scale use of either material for biological use is limited by two factors: ease of chemical modification and the paucity of knowledge of their surface chemistry in aqueous media. This thesis addresses aspects of both these issues. The first study reported is an in situ study of the adsorption dynamics of an exemplar globular protein (bovine serum albumin, BSA) on nanodiamond using the relatively novel quartz crystal microbalance with dissipation (QCM-D) technique. For the first time, QCM-D enabled the detailed study of protein dynamics (i.e. kinetics, viscoelastic properties, overlayer structure, etc.) onto nanodiamond thin films having various surface chemistry and roughness. The dynamics of protein adsorption is found to be sensitive to surface chemistry at all stages of adsorption, but it is only sensitive to surface roughness during initial adsorption phases. Our understanding of the nanodiamond-biology interface is enhanced by this study, and it suggests that QCM-D is useful for the study of the surface chemistry of nanoparticle forms of inorganic materials. A second study concerns a novel surface functionalization scheme, based on carbene and azo-coupling chemistry, which has been recently introduced as a practical, facile method for modifying the surfaces of polymers. Using modern surface characterization techniques, it is demonstrated that a chemical linker can be attached to polystyrene surfaces using carbene-based chemistry, and that further chemical functionality can be added to this chemical linker via an azo-coupling reaction. In situ studies of protein dynamics at these interfaces were conducted using QCM-D, thus enabling a link between specific protein behaviour and the polymer surface chemical termination chemistry to be made. A third area of study of investigates the use of diamond electrodes as a bio-sensor for dopamine under physiological conditions. For these conditions, ascorbic acid interferes with the dopamine oxidation signal, in ways that render the two signals irresolvable. Various modifications are used in attempts to reduce this interference, including: small and large cathodic treatments, grafting of electro-active polymers, addition of carbon nanotubes, and hydrogen plasma treatment. Those modifications leading to the hydrogen-termination of diamond are shown to work the best. Notably, hydrogen plasma treatment effects the complete electrochemical separation of dopamine and ascorbic acid at a diamond electrode. This is the first time this has been accomplished without adding non-diamond materials to the diamond electrode surface.